Hypothyroid associated megaesophagus in dogs: four years (2009- 2013) study in Hyderabad, India (Journal of Advanced Veterinary and Animal Research, 2015)
Megaoesophagus is uncommon but an important consideration for chronic regurgitation in dogs. Five dogs of various breeds were presented to the Teaching Veterinary Clinical Complex (TVCC) at College of Veterinary Science, Hyderabad with signs of chronic regurgitation, loss of weight, lethargy, weakness, dehydration and abnormalities of skin, and hair coat were diagnosed for megaesophagus on barium meal contrast radiography. At the TVCC, radiography and gastroscopy were performed, and the condition was confirmed as megaesophagus. Ancillary hemato-biochemical evaluations revealed normocytic normochromic anemia and mild leukocytosis with normal enzymatic activity in liver and kidneys. The thyroid profile in 80% (n=4/5) dogs showed decreased T3 and T4, and elevated thyroid stimulating hormone (TSH) levels confirming hypothyroidism. Ultrasonography of abdomen eliminated obstructions in the gastro-intestinal tract and other systemic conditions. Echocardiographic observations were normal in all the dogs. Treatment with metoclopramide (dosed at 5 mg/kg bwt) and levothyroxine (dosed at 20 ?g/kg bwt) and modified management practices involving feeding and diets were successful in controlling the regurgitation in dogs and resulted in good clinical recovery within 20- 30 days of post-treatment.http://dx.doi.org/10.5455/javar.2015.b69